Listeriosis: The Experience of a Portuguese Hospital Centre : Listeriose: A Experiência de um Centro Hospitalar Português - Costa, Andreia (2024)
Introduction: Listeria spp. infection is rare. It usually results from the consumption of contaminated food. Although most cases are sporadic, outbreaks of food origin have been reported. The spectrum of clinical manifestations is diverse, particularly bacteriemia, sepsis, and central nervous system (CNS) infection. It mainly affects elderly patients with important comorbidities or immunosuppression states, and pregnant women. Mortality can reach 30%. Material and Methods: We selected the specimens positive for strains of Listeria spp. using the laboratory informatic system database of our hospital center from 2013-2020. The patients’ corresponding processes were reviewed for demographic variables and clinical data as predisposing conditions, type of infection and outcome. Results: Twenty-five cases of Listeria infection were identified, with a mean age of 66.6 years. Most individuals (92%) had some risk factor or predisposing condition, with the most frequent being age > 65 years (64%), followed by the use of proton pump inhibitors, diabetes, alcoholism, neoplasia, and immunosuppressive therapy. Nineteen cases of bacteriemia and 9 cases of CNS infection were observed, and focal forms such as endocarditis, spontaneous bacterial peritonitis and infected muscle hematoma were observed. Overall mortality was 16%. No patient with CNS infection has died. Only in one case was there a relationship with a possible food outbreak. Conclusion: In our series, we found data similar to those in the literature, but we highlight the high percentage of patients with multiple predisposing conditions, less common focal forms, and the absence of mortality in patients with CNS infection. The analysis of our data allowed us to understand the importance of clarifying the source of infection, which is why we advise the use of a questionnaire regarding the consumption of suspicious food or an outbreak of food origin.